INOVASI PEDAGOGIS DALAM GERAKAN DAKWAH ISLAM: STUDI ETNOGRAFI PRAKTIK PEMBELAJARAN DI KOMUNITAS WAHDAH ISLAMIYAH - Agusman; Samsuddin; Abdurrahman (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2026)
The transformation of educational practices in the context of Islamic da’wah requires pedagogical innovations capable of responding to social dynamics and community-based learning needs. This study aims to analyze the forms, processes, and factors influencing pedagogical innovation in learning practices within the Wahdah Islamiyah community. This research employs a qualitative approach with an ethnographic strategy to gain an in-depth understanding of learning practices in the real-life context of the community. Data were collected through participant observation, in-depth interviews, and documentation, and were analyzed using thematic analysis techniques. The findings indicate that pedagogical innovation is manifested through participatory learning, the integration of religious values into social practices, the role of da’i as facilitators and role models, and the strengthening of a sustainable cadre system. In addition, learning takes place contextually through both formal and informal interactions that shape collective identity and individual transformation. This study contributes to expanding the perspective of Islamic education by positioning da’wah as a dynamic, community-based pedagogical practice, and offers practical implications for developing more adaptive, contextual, and learner-oriented learning strategies.